Aceroside VIII is a New Natural Selective HDAC6 Inhibitor that Synergistically Enhances the Anticancer Activity of HDAC Inhibitor in HT29 Cells - Ryu, Hyun-Wook; Lee, Dong-Hun; Shin, Dong-Hee; Hyun Kim, Seung; Kwon, So Hee (Planta Medica, 2015)
The identification of new isoform-specific histone deacetylase inhibitors is important for revealing the biological functions of individual histone deacetylase and for determining their potential use as therapeutic agents. Among the 11 zinc-dependent histone deacetylases that have been identified in humans, histone deacetylase 6 is a structurally and functionally unique enzyme. Here, we tested the inhibitory activity of diarylheptanoids isolated from Betula platyphylla against histone deacetylase 6. Aceroside VIII selectively inhibited histone deacetylase 6 catalytic activity and the combined treatment of aceroside VIII or (−)-centrolobol with A452, another selective histone deacetylase 6 inhibitor, led to a synergistic increase in levels of acetylated α-tubulin. Aceroside VIII, paltyphyllone, and (−)-centrolobol synergistically enhanced the induction of apoptosis and growth inhibition by A452. Consistent with these results, A452 in combination with aceroside VIII, paltyphyllone, or (−)-centrolobol was more potent than either drug alone for the induction of apoptosis. Together, these findings indicate that aceroside VIII is a specific histone deacetylase 6 inhibitor and points to a mechanism by which natural histone deacetylase 6-selective inhibitors may enhance the efficacy of other histone deacetylase 6 inhibitors in colon cancer cells.
Keywords: histone deacetylase 6; HDAC6-selective inhibitor; aceroside VIII; colon cancer; apoptosis; combination therapy